Power retail : winning strategies from Chapters and other leading retailers in Canada - Stevenson, Lawrence N. (McGraw-Hill, 2000)
Why power retaillers succeed despite the odds; The basis for strategy-customer segmentation; The essence of retail differentiation-The retail value proposition...